Neglect of the husband of the wife and vice versa and educational methods of treatment (Journal of the College of Basic Education, 2024)
neglect Consider avoiding family problems that often negatively affect the upbringing of children. Neglect leads to a threat to the life of the family. This behavior takes many forms, including the loss of dialogue with children, children’s distance from what is right, and the lack of a righteous upbringing, which leads to family disintegration, as Islamic Sharia calls for care Imam al-Sadiq, peace be upon him, said: “He who is kind to his family, may God increase his life.”